Diagnostic Accuracy and Clinical Utility of InaTB-Rif, Locally Developed Molecular Test for Tuberculosis, in Comparison with Xpert MTB/RIF in Indonesia - Handayani, Diah; Haryanto, Budi; Adyasiwi, Galoeh; Dahlan, Muhammad Sopiyudin; Agustin, Heidi; Wardoyo, Muhammad Prasetio; Ilham, Ahmad Fadhil; Burhan, Erlina (Jurnal Respirologi Indonesia, 2025)
Background: Tuberculosis (TB) remains a significant public health issue in Indonesia. Early and accurate diagnosis and drug susceptibility testing are essential for TB management. This study compared the diagnostic accuracy of the locally developed InaTB-Rif molecular test and Xpert MTB/RIF, using Mycobacterium Growth Indicator Tube (MGIT) culture as the reference standard. Methods: A cross-sectional study was conducted at Persahabatan Hospital, Jakarta, from February to August 2023. Presumptive pulmonary TB patients were recruited and tested using Xpert MTB/RIF, InaTB-Rif, and MGIT culture. The study assessed the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and agreement between InaTB-Rif and Xpert MTB/RIF for Mycobacterium tuberculosis (MTB) detection and rifampicin resistance. Diagnostic accuracy was compared using receiver operating characteristic (ROC) curves. Results: MGIT culture identified 29 TB-positive and 26 TB-negative cases. InaTB-RIF showed a sensitivity of 93.1% (95% CI=0.77-0.99), specificity of 76.9% (95% CI=0.56-0.91), PPV of 81.8% (95% CI=0.64-0.93), and NPV of 90.9% (95% CI=0.70-0.98). Xpert MTB/RIF had a sensitivity of 89.7% (95% CI=0.726-0.978), specificity of 80.8% (95% CI=0.606-0.93), PPV of 83.9% (95% CI=0.66-0.94), and NPV of 87.5% (95% CI=0.67-0.97). The area under the curve (AUC) was 0.8501 for InaTB-RIF and 0.8521 for Xpert MTB/RIF, with no significant difference in accuracy (P=0.965). The kappa value for MTB detection was 0.776, indicating substantial agreement, while the kappa value for rifampicin resistance detection was 0.517, indicating moderate agreement. Conclusions: InaTB-RIF demonstrates comparable diagnostic accuracy to Xpert MTB/RIF with good diagnostic performance and agreement for detecting MTB and moderate agreement for rifampicin resistance detection.